Economic growth in England, 1250-1850: Some new estimates using a demand side approach - Alessandro Nuvolari (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2011)
Using the demand side approach we construct a new set of estimates of per capita agricultural output and per capita GDP for England over the period 1250-1850. Our estimates of per capita GDP suggest that the pattern of long run growth of the English economy can be interpreted with a periodization in three historical stages. The first stage, covering the period 1250-1580, is a Malthusian phase with no positive growth. The second stage, comprising the period 1580-1780, is an intermediate phase where the English economy is able to relax some of the Malthusian constraints, attaining a positive growth rate (although our estimate of the growth rate for this period is lower than that proposed by Maddison and more recently by Broadberry, Campbell, Klein, Overton and van Leeuwen). The third stage covering the post 1780 period is represented by the industrial revolution and by the definitive consolidation of a development pattern characterized by a steady positive growth rate.
Keywords: N13; O47; 330; GDP; Economic growth; England